Peran Customer Satisfaction Dalam Memediasi Pengaruh Service Quality, Perceived Enjoyment, dan Trust Terhadap Customer Loyalty Pada Pembelian Paket Data Telkomsel - Muhammad Syahrul Faturachman; Suryati (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the mediating role of customer satisfaction in the relationship between service quality, perceived enjoyment, trust, and customer loyalty among Telkomsel data package users in Surakarta. Using a quantitative approach with 100 purposively selected respondents, data were analyzed through PLS-SEM. Findings reveal that service quality, enjoyment, and trust significantly influence both satisfaction and loyalty. Customer satisfaction also mediates these relationships. The study offers practical insights for telecom providers to enhance service quality, foster enjoyable user experiences, and build trust to sustain customer loyalty.